Metode Dan Strategi Dalam Sistem Pembelajaran Daring Guru Ummi Smp Islam Darussalam Pada Masa Pandemi Covid -9 - Rahmayanti, Carina; Pramesti, Darti; Amirullah, Muhammad (LP2M IAIN Sultan Amai Gorontalo, 2021)
The development of education today is influenced by the rapid progress of information and communication technology. One of the information technologies that play a role in the world of education is online learning. Online learning functions as a liaison between educators and students via the internet network that can be accessed anytime and anywhere. The online media used in this research are various, such as WhatsApp, Google Classroom, Zoom, and Websites. The purpose of this study was to determine online learning methods and strategies during the Covid-19 pandemic. This research is a descriptive-analytical study. Data collection techniques using documentation and interviews. The result of this research is that learning the Al-Qur'an method of UMMI SMP Islam Darussalam is good because it continues to be supervised every 2 months by the director of the central UMMI Foundation, but the most important thing is that schools must continue to play more roles to control their students to continue to attend. using zoom and also the role of parents at home who continue to supervise their children entering school or not, so that with the supervision of schools and their parents, plus good quality methods will result in good, quality and efficient learning.